Effects of plant-growth promoting rhizobacteria on growth and physiological activities of cucumber - LIANG Jian-gen; ZHANG Bing-xin; YU Jing-quan; CHEN Zhen-yu (浙江大学学报. 农业与生命科学版)
In order to explore the functionary mechanism of plant growth-promoting rhizobacteria (PGPR) CH1 and CH2 to cucumber growth and quality, the seed germinating, greenhouse pot planting and physiological and biochemical methods was employed to study the effects of CH1 and CH2 on growth and physiological metabolism of cucumber. Results showed that PGPR CH1 and CH2 obviously promoted germinating of cucumber seeds, root and plant growth, as well as the superoxide anion—producing rate, contents of H2O2 and MDA in roots and leaves of cucumber were considerably decreased after treatment with CH1 and CH2, contents of chlorophyll, protein, soluble sugar and Vc which are related with cucumber quality were magnificently increased.